A cross-country qualitative study on contraceptive method mix: contraceptive decisionmaking among youth - Lynette Ouma; Burcu Bozkurt; Jill Chanley; Christine Power; Ronald Kakonge; Oluwatosin C. Adeyemi; Ramya Jawahar Kudekallu; Elizabeth Leahy Madsen (BMC, 2021)
Plain Language Summary Despite increased international and national commitments to improving young people's access to contraception, youth ages 15 to 24 face significant barriers to accessing a full range of contraceptive methods. This study conducted in-depth interviews with key stakeholders and focus group discussions with youth in Kenya, Nigeria, and Uganda to understand what factors impact youth's decision to use or not use certain contraceptive methods. In all three countries, youth reported that condoms are the most commonly sought contraceptive method because they are easiest to access and because youth have limited knowledge of other methods. Youth from diverse settings shared uncertainty and concern about the safety and side effects of many methods other than condoms. While most youth in Kenya, Nigeria, and Uganda reported at least moderate confidence in obtaining the information needed to help choose a method, other barriers like cost, inconvenient facility hours and long wait times, and stigma from family, community members, and providers still present a major deterrent for youth who want information on contraceptive methods. Program implementers and policymakers should consider the diverse and often interconnected barriers that youth face in attempting to enjoy the benefits of a full spectrum of contraceptive methods and design multi-level interventions to mitigate such barriers.